Increased bleeding risk with phosphodiesterase‐5 inhibitors after left ventricular assist device implantation. (5th April 2021) - Jakstaite, Aiste‐Monika; Luedike, Peter; Schmack, Bastian; Pizanis, Nikolaus; Riebisch, Matthias; Weymann, Alexander; Kamler, Markus; Ruhparwar, Arjang; Rassaf, Tienush; Papathanasiou, Maria
Abstract: Aims: Therapy with phosphodiesterase‐5 inhibitors (PDE5Is) after left ventricular assist device (LVAD) implantation has been associated with lower mortality and device thrombosis but increased risk for post‐operative and gastrointestinal bleeding. We aimed to evaluate the impact of long‐term PDE5Is on the overall bleeding risk after LVAD implantation. Methods and results: We retrospectively included patients who received a continuous‐flow LVAD at our site and were prescribed with long‐term oral PDE5Is after discharge from the index hospitalization. The primary endpoint was the occurrence of bleeding at 12 month follow‐up. Secondary endpoints were all‐cause death and the combination of bleeding and all‐cause death. Our analysis included 109 patients of whom 75 (69%) received long‐term PDE5Is. Mean age was 56 years, and 85% were male. At 12 months, 19 (17%) patients experienced at least one bleeding event. Patients on PDE5Is had higher bleeding rates (23% vs. 6%, P  = 0.03) and more bleeding events per patient‐year (0.32 vs. 0.06, P  = 0.03) compared with patients not on PDE5Is. While overall bleeding incidence was excessively higher in the PDE5I group, there were no significant differences in the incidence of major bleeding (19% vs. 6%, P  = 0.08) and gastrointestinal bleeding (11% vs. 3%, P  = 0.18). Kaplan–Meier analysis revealed higher cumulative incidence of bleeding for the PDE5I group (log rank = 0.04) with no difference on all‐cause death (log rank = 0.67) and the combination of bleeding and all‐cause death (log rank = 0.13). Hospitalizations for bleeding and their duration were numerically higher in the PDE5I group (0.28 vs. 0.03, P  = 0.07 and 2.4 vs. 0.2, P  = 0.07, respectively). Conclusions: Phosphodiesterase‐5 inhibitor treatment after LVAD implantation is associated with increased bleeding risk after LVAD implantation. The safety of long‐term PDE5Is in LVAD patients remains unclear and needs to be further clarified in prospective studies with randomized study design.